Analisis Risiko pada Proyek Pembangunan Parkir Basement Jalan Sulawesi Denpasar - Muka, I Wayan (Department of Civil Engineering, Diponegoro University, 2013)
Construction of Basement Parking Sulawesi Road Denpasar is a government attempt to tackle congestion and parking problems in the city of Denpasar. This activity is highly correlated with the location of Badung Market. This study aims to identify risks arising, assess the level of acceptance of risk analysis, risk mitigation and ownership of dominant risk. The results showed 25 risks identified. Of the risks identified are 24 risk dominant with 5 risk category is unacceptable occurrence of accidents in the project, the landslide during basement excavation, the lack of security fence project that can cause accidents especially hazard fell during basement excavation, the damage caused by natural disasters and the workers were not using safety equipment. Additionally identified 19 risk category is undesirable, one acceptable risk category. Dominant risk is unacceptable risks do 11 mitigation measures such as building damage due to natural disasters (force majeure), which is also a risk with follow-up by reducing the risk that anticipated early preparing for disasters and transfer risk to another party by insuring the work to others. Ownership is the most dominant risk of the contractor. The parties should consider the risks unacceptable category and also should pay attention to the risks classified as undesirable.